Bridging Gaps in English Writing: Syntactic, Lexical, Discourse, and Cognitive Challenges among Thai University Students - Delgado, Don August (Journal of English Education, 2025)
Writing in English is widely regarded as the most demanding communicative ability among Thai undergraduates because it requires simultaneous control of grammar, lexis, rhetorical organization, and content, while also mobilizing the cognitive processes used in listening, reading, and speaking. To identify how this competence can be strengthened, the present quantitative study investigated eighty students whose degree programmes are delivered exclusively in English, making them an appropriate cohort for analysing difficulties in four domains: (1) syntactic competence, (2) lexical competence, (3) discourse competence, and (4) cognitive competence. Descriptive statistics, one-way analysis of variance (ANOVA), and Pearson correlation were applied. Self-assessment data revealed strong positive correlations among all competence indicators on both ANOVA and Pearson tests, suggesting that perceived proficiency in one domain is closely linked to proficiency in the others. Reported writing challenges similarly showed significant interrelationships through Pearson analysis, yet ANOVA detected no significant group differences, indicating wide individual variation. When overall self-assessed competence was correlated with overall perceived challenges, the Pearson coefficient showed no meaningful relationship, implying that students who feel highly competent may still experience specific obstacles, and vice versa. These findings highlight the need to reassess and refine pedagogical approaches to English writing for Thai university learners, with targeted, domain-specific support aimed at integrating syntactic, lexical, discourse, and cognitive skills to foster balanced, sustainable growth in academic writing performance. Therefore, curriculum designers, language teachers, and policymakers should collaborate in developing adaptive writing curricula informed by data-driven insights.